Handcrafted Indian textiles : tradition and beyond - Singh, Martand (New Delhi : Lustre Press, Roli Books, 2000)
"The outstanding textiles represented in this book were displayed at the Visvakarma series of exhibitions and have a wide-ranging vocabulary of design, technical skill and aesthetic brilliance. Written and edited by renowned names in textile design, this book is, indeed, a treasure for both the textile aficionado and designer."--
Keywords: Textile fabrics; Textile design; Decorative arts